Self-Organising Systems in the Context of Academic Environment - T. V. Kuprina; A. P. Beketova; S. M. Minasyan (Obrazovanie i Nauka)
Introduction. In the era of globalisation, which affects all spheres of modern social life (political, financial, scientific, technical, religious, cultural), the processes of internationalisation and academic migration in higher education have significantly intensified. The rapidly growing mobility in higher education, when students study outside their country of residence, is accompanied by certain problems, which include students’ adaptation to the conditions of unfamiliar urban environment. The introduction of new methodological tools for teaching humanitarian disciplines in universities can contribute to the elimination of barriers and successful transition of students to another, different from their customary, socio-cultural environment.The aim of the research was to present the results of experimental work aimed at the development of students’ intercultural communicative tolerance within the foreign language learning, and to reveal the role of self-organising systems in the university international academic environment.Methodology and research methods. The study is based on the theory of self-organising systems. In the process of designing and application of the authors’ technology aimed at developing students’ intercultural communicative tolerance, experimental methods and the method of comparative analysis were used.Results and scientific novelty. It has been shown that academic migration is a self-organising system characterised by socio-cultural instability. The factors of human transition from one urboecological niche to another, which often disturbs the balance of social systems, have been described. Lacking knowledge about such processes in the theory and practice of pedagogy within higher education has been stated. Insufficient level of intercultural communicative tolerance of Russian (132 people) and foreign (40 people) students, who studied at the Ural Federal University (Ekaterinburg, Russia) in 2015, has proved the necessity of its systematic focused formation. The technology for the development of this type of tolerance within the framework of the ‘Foreign Language’ discipline has been proposed. The approbation of the technology has demonstrated its effectiveness. The students have not only acquired the necessary competencies, but also learned to adapt to the new academic environment, as well as had the opportunity to directly participate in the creation of their own academic programs.Practical significance. The research confirms the productivity of mutual adaptation of students to an unfamiliar socio-cultural academic environment. The author’s technology of intercultural communicative tolerance development can be used to optimise the pedagogical conditions of maintaining the processes of internationalisation and academic mobility within universities.